Penerapan Pendidikan Literasi Akuntansi Dalam Peningkatan Kinerja UMKM Rengginang Singkong KWT Rukun Makaryo Desa Kedungdowo - Armiawan, Muhammad Edward Putra; Yodanto, Dandi Setio; Handayani, Wahyu Tri; Azzahra, Hanifah Rizqi (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Cassava rengginang MSMEs still have many obstacles in running their business. These obstacles can cause problems in the sustainability of MSMEs that need to be found a solution. The main problem that is an obstacle in the continuity of their business is the absence of recording of production costs. This is due to the difficulty of MSME actors in starting to record production costs and their lack of awareness about the importance of recording expenses. In running their business, MSME actors only sell their products at product prices that adjust market prices, so they do not take into account the capital they spend during the production period which has an impact on obtaining maximum profit. The purpose of this activity is to raise awareness to MSME actors in Keudungdowo Village to start recording finances and provide media for recording production costs to make it easier for MSME actors to carry out financial management. From this activity, it is hoped that it can help the village government in maintaining the sustainability of community MSMEs,